(untitled) - Mason, Diana J. (St. Louis, MO, 2002)
Contents: Introduction to policy and politics in nursing and health care, Health care delivery and finacing, Policy and politics in the workplace, Policy and politics in government,Policy and politics in professional organizations, Policy and politics in the community.
Keywords: Nursing,Y tá; Political aspects,Khía cạnh chính trị; United States,Hoa Kỳ